Efficiently electrochemical CO2 reduction on molybdenum-nitrogen-carbon catalysts with optimized p-block axial ligands; Chemical Engineering Science; Vol. 273 - Liu Yingnan; Wang Dashuai; Bin Yang; Li Zhongjian; Peng Xianyun; Liu Zhibin; Zeng Libin; Zhang Tao; Rodriguez (Rodriges) Contreras R. D. Raul David; Lei Lecheng; Hou Yang (2023, 2023)
Title screen